Pelaksanaan kelas disleksia (program rintis) di Malaysia - Philips Susanna Clare, Razalli Abdul Rahim, Kway Eng Hock, Ahmad Noor Aini, Muhammad Kamaliah, Yusuf Md Fawzi, (Universiti Pendidikan Sultan Idris, 2005)
Pelaksanaan kelas disleksia (program rintis) di Malaysia by Philips Susanna Clare, Razalli Abdul Rahim, Kway Eng Hock, Ahmad Noor Aini, Muhammad Kamaliah, Yusuf Md Fawzi,